The plasminogen receptor, Plg-R(KT), plays a role in inflammation and fibrinolysis during cutaneous wound healing in mice - Ny, Lina (Cell Death Dis, 2020)
Wound healing is a complex physiologic process that proceeds in overlapping, sequential steps. Plasminogen promotes fibrinolysis and potentiates the inflammatory response during wound healing. We have tested the hypothesis that the novel plasminogen receptor, Plg-R(KT), regulates key steps in wound healing. Standardized burn wounds were induced in mice and time dependence of wound closure was quantified. Healing in Plg-R(KT)(−/−) mice was significantly delayed during the proliferation phase. Expression of inflammatory cytokines was dysregulated in Plg-R(KT)(−/−) wound tissue. Consistent with dysregulated cytokine expression, a significant delay in wound healing during the proliferation phase was observed in mice in which Plg-R(KT) was specifically deleted in myeloid cells. Following wound closure, the epidermal thickness was less in Plg-R(KT)(−/−) wound tissue. Paradoxically, deletion of Plg-R(KT), specifically in keratinocytes, significantly accelerated the rate of healing during the proliferation phase. Mechanistically, only two genes were upregulated in Plg-R(KT)(−/−) compared with Plg-R(KT)(+/+) wound tissue, filaggrin, and caspase 14. Both filaggrin and caspase 14 promote epidermal differentiation and decrease proliferation, consistent with more rapid wound closure and decreased epidermal thickness during the remodeling phase. Fibrin clearance was significantly impaired in Plg-R(KT)(−/−) wound tissue. Genetic reduction of fibrinogen levels to 50% completely abrogated the effect of Plg-R(KT) deletion on the healing of burn wounds. Remarkably, the effects of Plg-R(KT) deletion on cytokine expression were modulated by reducing fibrinogen levels. In summary, Plg-R(KT) is a new regulator participating in different phases of cutaneous burn wound healing, which coordinately plays a role in the interrelated responses of inflammation, keratinocyte migration, and fibrinolysis.